Membentuk Karakter Generasi Muda Melalui Institusi Keluarga Di Era Digital - Salmawaty RG; Hilal Mahmud (Institut Agama Islam Negeri (IAIN) Palopo, 2017)
The main focus of this research is how to shape character of young generation through family institutions in digital era. The study, therefore, discusses the adopted parenting pattern and the role of family institutions in shaping character of young generation in digital era. Data obtained through questionnaires, interviews, observation and documentation studies. The population in this study is all students of SMP Negeri 9 Palopo which amounted to 597 people. Sampling technique used is Probability Sampling Technique based on Slovin formula so that the number of samples is 86 people. The results showed that the adopted parenting pattern is permissive, authoritarian, and authoritative.